Improving Engineering Students' Learning Outcomes With The Mind Mapping Learning Model - Setiawan, Doni (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study aims to improve the learning outcomes of engineering students in applied physics courses using the Mind Mapping learning model at the Muhammadiyah University of Tegal. This study involved the stages of planning, action, observation, and reflection. The results showed an increase from the initial conditions, where 11 students or 39% of the student group reached the level of completion, while 17 students or 61% of students did not achieve completion. In cycle I, there was a significant increase with 15 students or 54% reaching the level of completion, while 13 students or 46% of students did not achieve completion. In cycle II, further improvements were made from cycle I and finally reached a full level of completion with 26 students or 93% of students achieving completion and the remaining 2 students or 7% did not complete. Based on the results of this study, it can be concluded that the application of the Mind Mapping learning model has a significant positive impact on improving student learning outcomes.